2022
DOI: 10.1038/s41598-022-26662-5
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in Marfan syndrome mice is restored by resveratrol

Abstract: Patients with Marfan syndrome (MFS) develop thoracic aortic aneurysms as the aorta presents excessive elastin breaks, fibrosis, and vascular smooth muscle cell (vSMC) death due to mutations in the FBN1 gene. Despite elaborate vSMC to aortic endothelial cell (EC) signaling, the contribution of ECs to the development of aortic pathology remains largely unresolved. The aim of this study is to investigate the EC properties in Fbn1C1041G/+ MFS mice. Using en face immunofluorescence confocal microscopy, we showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…These morphological changes may have a compound effect in vessels where the ratio of endothelial cells to smooth muscle cells is increased, such as in smaller vessels like cerebral arteries. In addition, aging also plays a role in decline of endothelial cell junctional linearity and reduction in endothelial cell surface area, which may contribute to vascular permeability such as increased blood–brain barrier permeability displayed in normal aging 57 . Thus, this change in endothelial cell morphology could contribute to the changes seen in the posterior cerebral artery blood flow velocity in MFS and 12M CTRL mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These morphological changes may have a compound effect in vessels where the ratio of endothelial cells to smooth muscle cells is increased, such as in smaller vessels like cerebral arteries. In addition, aging also plays a role in decline of endothelial cell junctional linearity and reduction in endothelial cell surface area, which may contribute to vascular permeability such as increased blood–brain barrier permeability displayed in normal aging 57 . Thus, this change in endothelial cell morphology could contribute to the changes seen in the posterior cerebral artery blood flow velocity in MFS and 12M CTRL mice.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in endothelial function have be measured in MFS patients through flow-mediated dilation, which is negatively correlated with the diameter of the thoracic aorta 75 . In MFS mice, using en face analysis of the aorta, it was also shown that endothelial cell alignment with blood flow was reduced, endothelial cell roundness was increased, individual endothelial surface area was increased, and endothelial cell junctional linearity was decreased 57 .…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that flow-mediated responses were impaired in Marfan patients 42 and a negative correlation was observed between flow-mediated dilation and the diameter of ascending thoracic aorta 43 . In addition, it has previously been shown that Marfan model mice (Fbn1 C1041G/+ ) show alteration of EC morphology with a rounder shape and reduced alignment to blood flow 44 and reduction of basal NO production in older animals 45 . The abnormal EC phenotypes with upregulation of ICAM-1 and VCAM-1 are observed as early as 1 week of age before manifestation of the gross phenotype in AD mouse aortas, supporting the notion that the activation of ECs with abnormal mechanosensing contributes to the upregulation of adhesion molecules and triggers the recruitment of bone marrow-derived monocytes/macrophages into the intima.…”
Section: Discussionmentioning
confidence: 99%
“…Further emphasising the importance of the ECM, Marfan syndrome, defined by mutations in the ECM component fibrillin-1 (FBN1), presents with an increased risk of aortic aneurysm ( Pereira et al, 1997 ; Dietz and Pyeritz, 1995 ). Introducing the Marfan-specific mutation Fbn1 C1041G specifically into murine ECs impaired their alignment within both the ascending and descending aorta, and perturbed junctional stability under LF ( Mieremet et al, 2022 ). The same study showed that treatment with resveratrol restored EC alignment, phospho-eNOS expression and vascular structure, effectively rescuing the phenotype.…”
Section: Consequences Of Impaired Endothelial Mechanosensingmentioning
confidence: 99%